Eye Laceration in a Horse - Angell, J. A. (Veterinary and Comparative Orthopaedics and Traumatology, 1991)
A case study is presented of a Hanoverian filly with a corneo-scleral laceration. The lesion was the result of self-inflicted trauma. Medical treatment was instituted for the first twenty-four hours after the injury. Aggressive surgical treatment was necessary to attempt to save the eye and for the future use of a cosmetic scleral shell.The owner of the filly decided upon surgical repair of the corneo-scleral laceration and the eventual use of a cosmetic scleral shell. As the filly matures, the shell will need to be enlarged in order to fill the enlarging orbit.
Keywords: Eye laceration; horse